Pemanfaatan Teknologi Pascapanen untuk Pengembangan Agroindustri Perdesaan di Indonesia - Akmadi Abbas; Rita Nur Suhaeti (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
EnglishPostharvest handling application is one of the ways to increase agricultural commodity’s added value. In addition, it also can reduce agricultural yield loss. Technology application is started with dissemination and socialization activity and then followed by technology adoption. The process of dissemination and adoption of the introduced technologies is a crucial part of the efforts to apply technology at the end user’s level. Various influencing factors on the process of dissemination and adoption are associated with the technology, dissemination process, and technology beneficiaries. This paper describes an analysis of post-harvest technology transfer process mainly for food crops and estate crops, and community development in various regions of Indonesia. A concept of zero waste development policy is enhanced in the process of disseminating postharvest technology toward development of rural agro-industry. With that action, it is expected that farmers' income and agricultural commodity competitiveness could be improved.IndonesianPenerapan teknologi pascapanen merupakan salah satu cara untuk meningkatkan nilai tambah komoditas pertanian. Selain itu, aplikasi teknologi pascapanen juga dapat menekan kehilangan hasil panen. Penerapan teknologi diawali dengan diseminasi teknologi, selanjutnya terjadi adopsi teknologi. Proses diseminasi dan adopsi teknologi ini merupakan bagian penting dalam pemanfaatan teknologi bagi pengguna. Berbagai faktor yang berpengaruh dalam proses diseminasi dan adopsi teknologi terkait dengan teknologi, proses diseminasi, dan penerima manfaat teknologi tersebut. Tulisan ini mendeskripsikan proses alih teknologi pascapanen produk tanaman pangan dan tanaman perkebunan serta pemberdayaan masyarakat pengguna teknologi pascapanen di berbagai daerah di Indonesia. Dalam proses mendiseminasikan teknologi pascapanen menuju pengembangan agroindustri di perdesaan dikembangkan konsep kebijakan yang diharapkan dapat meningkatkan pendapatan petani dan daya saing komoditas pertanian.